PELAKSANAAN PENDIDIKAN AKHLAK DALAM KELUARGA DI DESA TANIMULYA KECAMATAN NGAMPRAH KABUPATEN BANDUNG BARAT - Hana Fauziah (Universitas Pahlawan Tuanku Tambusai, 2022)
Early education which greatly influences the formation of a child's personality, of course, starts with family education. Because if the next educational environment is good, entering the education stage will be good, and vice versa. When the educational environment is negative when it is not good, it could be that children entering the next stage of education will be easily influenced to do something wrong. Morals are the most important factor to form a happy household. In the technical family, parents' activities will be used as role models for children in morals. The purpose of this study was to determine the process of implementing children's moral education in families in Tanimulya Village, Kec. Ngamprah Kab. West Bandung. The method used is descriptive qualitative method, the results of the study show that although parents are busy working, in the implementation of education Morals in the family have been successfully instilled, by looking at the morals seen in the behavior of the children of Tanimulya Village. Keywords: Education, Morals, Family.